2011
DOI: 10.1007/s12576-011-0145-z
|View full text |Cite
|
Sign up to set email alerts
|

Effect of ramp bicycle exercise on exhaled carbon monoxide in humans

Abstract: The effect of exercise on the increase of exhaled CO in smokers compared to non-smokers has not been clarified yet. In this study we compared the dynamics of exhaled CO before, during and after exercise between smokers and non-smokers. A group of 8 smokers and a group of 8 non-smokers underwent a bicycle exercise in a ramp fashion to near maximum intensity. Ventilation and gas exchange, and CO exhalation were continuously measured every 30-s before, during and after the exercise. The fraction of CO (F (CO)) in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 22 publications
1
3
0
Order By: Relevance
“…・ E against time in one non-smoker. Note that ∆FCO, gradually decreased, but V ・ CO increased during ramp exercise, similar to the changes of V ・ O 2 and V ・ E. This was reported by Yasuda et al 15) .…”
Section: The Effect Of Donors or Supplements For Gts On Cardiorespirasupporting
confidence: 86%
See 3 more Smart Citations
“…・ E against time in one non-smoker. Note that ∆FCO, gradually decreased, but V ・ CO increased during ramp exercise, similar to the changes of V ・ O 2 and V ・ E. This was reported by Yasuda et al 15) .…”
Section: The Effect Of Donors or Supplements For Gts On Cardiorespirasupporting
confidence: 86%
“…With respect to exhaled CO during exercise, Horbáth et al 13) reported a significant increase in exhaled CO output (V ・ CO) from rest to 60 W, and to maximal exercise in healthy children. Yasuda et al 15) also confirmed a linear increase of V ・ CO against workloads during a ramp exercise protocol in young male subjects as shown in Fig. 4.…”
Section: Effects Of Exercise and Exercise Training On The Exhalation mentioning
confidence: 57%
See 2 more Smart Citations